Effect of pre-harvest application of NAA and potassium nitrate on storage quality of winter guava (Psidium guajava) - MANDAL, GOUTAM; DHALIWAL, H S; MAHAJAN, B V C (The Indian Journal of Agricultural Sciences, 2014)
A study was conducted at Punjab Agricultural University, Ludhiana during 2006–08 in winter crop of guava cv. Sardar to evaluate the influence of pre-harvest foliar application of naphthalene acetic acid (NAA) and potassium nitrate on quality attributes in different interval of cold storage. The plants were sprayed with NAA and potassium nitrate at colour break stage of fruit and harvested at optimum maturity, packed in CFB boxes with newspaper lining and stored at 6- 8oC and 90-95% RH. Fruits treated with NAA (100 ppm) effectively reduced spoilage maintained higher fruit firmness, TSS and ascorbic acid and remain slightly desirable after 30 days of storage. Thus, pre-harvest spray with NAA (100 ppm) seems to be effective method for decreasing post- harvest losses and maintaining quality of guava fruits.